Entrainment and droplet spectral characteristics in convective clouds during transition to monsoon. (22nd March 2016) - Bera, Sudarsan; Pandithurai, G.; Prabha, Thara V.
Abstract: In situ observations in growing deep cumulus in polluted and clean environments during the transition to monsoon over Indian peninsula are used to investigate entrainment effects on droplet size distribution and the width of possible cloud cores. Pre‐monsoon clouds indicate reduction in spectral width in the diluted cloud volumes due to lateral entrainment whereas monsoon cloud has higher spectral width. Relative dispersion is observed to increase with the distance from cloud core of monsoon cloud while for pre‐monsoon clouds it remained almost constant. Enhanced entrainment in polluted pre‐monsoon clouds is responsible for narrow cloud core compared to monsoon cloud.